THE MEANING OF KHALAQA IN THE QUR’AN: TOSHIHIKO IZUTSU SEMANTIC - D. Zahra AS. FM; Apri Wardana Ritonga; Nisa Afrinauly Nabila; Sheni Nursopa (Tanzil: Jurnal Studi Al-Quran, 2023)
The word in the Qur'an that shows the meaning of creation is khalaqa. Even though these words refer to the meaning of creation, there are different meanings and uses contained in these words. This study uses a descriptive qualitative approach. The type of research used is library research. This research was conducted using data collection methods from the library, either in the form of books, journals, documents, magazines and so on. The data collection method in this study uses documentation. The analysis technique used is the semantic analysis approach developed by Toshihiko Izutsu. The purpose of this study is to reveal the meaning contained in the word khalaqa and reveal the world view of the Qur'an (weltanschauung) on that word. The process carried out in this study is to analyze the basic meaning of the word, then examine the relational meaning of the word khlaqa using syntagmatic and paradigmatic analysis, and then examine the use of the vocabulary of khalaq in the pre-Qur'anic, Qur'anic and post-Qur'anic periods by looking at the interpretations of the classical, medieval and modern periods. The results of the research show that the basic meaning of khalaqa in the Qur'an is to create. Semantically, the word khalaqa is closely related to other words in the Qur’an, such as the words Allah, al-arḍ and sama‘; al-insān; al-mawt and al-ḥayāt; azwaja, male and female, animals, jin, and kulla shay’in. The words that are synonymous with the word khalaqa in the Qur'an are ja‘ala, faṭara, bada‘a, shana‘a, and ṣawara. While the antonyms are the words ahlaka, dammara, amāta, azāla and afna. Second, the word khalaqa after analyzing its synchronic and diachronic meanings refers to creation in which Allah is the object.